Peran Mekanisme Pengawasan dalam Memediasi Hubungan antara Transparansi dan Akuntabilitas Pengelolaan Subsidi Publik - Coelho, Agostinho; Rodriques, Julião Henriques; Pinto, Mateus; Pereira, Benigno (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the mediating role of oversight mechanisms in the relationship between transparency and accountability in the management of public subsidies in Timor-Leste. The research addresses the gap that increased transparency does not automatically lead to substantive accountability without effective oversight. A quantitative explanatory approach was employed, using questionnaire data collected from 46 officials involved in public subsidy management at the Ministry of Higher Education, Science, and Culture of Timor-Leste. Data were analyzed using path analysis with SPSS software. The findings show that transparency has a positive and significant effect on oversight mechanisms (β=0.739) and on accountability (β=0.837). Oversight mechanisms also have a positive and significant effect on accountability (β=0.594) and fully mediate the relationship between transparency and accountability (indirect effect = 0.509). The implications confirm that transparency alone is insufficient to ensure accountable public subsidy governance without effective oversight systems. This study recommends strengthening internal and external oversight mechanisms, enhancing auditor capacity, and developing digital-based oversight to improve the effectiveness and credibility of public subsidy management in Timor-Leste.